Active ray-curable composition, active ray-curable ink composition and method for producing them
Patent Information
- Application Number
- JP2023113927
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-11
- Publication Date
- 2025-01-24
AI Technical Summary
【0013】 本発明の活性光線硬化型組成物及び活性光線硬化型インキ組成物は、有機溶剤を含まず、柔軟性、塗膜の透明性、密着性に優れる。従って、塗布や印刷の際に溶剤を熱乾燥させる工程が不要であり、環境に対する懸念も少ない。 本発明の活性光線硬化型組成物は、優れた柔軟性、透明性、及び密着性を有する塗膜を提供することから、プラスチック、紙、ガラス、木工及び無機材料等の塗料、コーティング剤、包装材料用、表示材料用、電子材料用あるいは光学材料用の硬化接着剤、スクリーン印刷、オフセット印刷、ロールコーター印刷、インクジェットインク、プライマーインク等の印刷インキ等の様々な用途に広く使用することが可能である。
Smart Images

Figure 2025011681000001 
Figure 2025011681000002 
Figure 2025011681000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an actinic radiation-curable composition containing a vinyl chloride-vinyl acetate copolymer, an actinic radiation-curable ink composition, and methods for producing the same. [Background technology]
[0002] Conventionally, actinic radiation-curable compositions that are cured by actinic radiation such as ultraviolet rays or electron beams have been put to practical use in various applications such as paints, coating agents, adhesives, printing inks, ink-receptive layers, printed circuit boards, and electrical insulation for plastics, paper, glass, woodworking, and inorganic materials, etc. In particular, actinic radiation-curable inks have attracted attention due to their quick drying properties and the ability to record on recording media with poor ink absorbency.
[0003] Such actinic radiation-curable compositions are required to have excellent flexibility and adhesion, and therefore, various methods have been proposed to date for improving the flexibility and adhesion of actinic radiation-curable compositions.
[0004] For example, JP 2010-006878 A (Patent Document 1) discloses an active energy ray-curable ink composition in which an active energy ray-curable ink is mixed with a varnish in which a thermoplastic resin having a glass transition temperature of 50 to 250° C. is dissolved in a solvent.
[0005] However, since this active energy ray-curable ink composition contains a solvent, a step of thermally drying the solvent is essential, and furthermore, the solvent may remain in the ink after printing, which may have an adverse effect on the environment.
[0006] On the other hand, as an example of an actinic radiation-curable ink that does not contain a solvent, JP 2009-197156 A (Patent Document 2) discloses a cationic polymerization type inkjet ink that contains 0.3% by mass or more and 5.0% by mass or less of a vinyl chloride-vinyl acetate copolymer having a number average molecular weight of 14,000 or more and 25,000 or less.
[0007] However, although the cationic polymerization type inkjet ink described in Patent Document 2 is said to have excellent adhesion, there is room for improvement. In addition, the ink in Patent Document 2 has poor flexibility and is not suitable for applications requiring greater flexibility.
[0008] In addition, it is also important that actinic radiation curable compositions used for various applications have little deterioration over time and excellent thermal stability. JP2018-135483A (Patent Document 3) discloses an actinic radiation curable composition having excellent flexibility, adhesion, and thermal stability. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2010-006878 A [Patent Document 2] JP 2009-197156 A [Patent Document 3] JP 2018-135483 A Summary of the Invention [Problem to be solved by the invention]
[0010] However, although the actinic radiation-curable composition described in Patent Document 3 has high flexibility and adhesion, the transparency of the coating film may be poor and the coating film resistance, such as alcohol resistance, may be poor, leaving room for improvement. The present invention has been made in view of the above circumstances, and an object of the present invention is to provide an actinic radiation-curable composition, an actinic radiation-curable ink composition, and methods for producing the same, which do not contain an organic solvent and have excellent flexibility, coating film transparency, and adhesion. [Means for solving the problem]
[0011] As a result of extensive investigations to achieve the above object, the present inventors have found that an actinic radiation-curable composition excellent in flexibility, transparency of the coating film, and adhesion can be obtained by dissolving a vinyl chloride-vinyl acetate copolymer in a photocurable monomer and / or oligomer, and have thus completed the present invention.
[0012] That is, the present invention provides the following actinic radiation-curable composition, actinic radiation-curable ink composition, and methods for producing the same. [1] An actinic radiation-curable composition comprising (I) a vinyl chloride copolymer and (II) a photocurable monomer and / or oligomer, the vinyl chloride copolymer (I) containing, as a structural unit, the following relative to the mass of the vinyl chloride copolymer: (a) 82 to 95 mass% of vinyl chloride-derived units, (b) 0.1 to 5% by mass of units derived from vinyl acetate, and (c) hydroxyl group-containing vinyl-derived unit: 4 to 15% by mass and is free of organic solvent. [2] The actinic radiation-curable composition according to the above [1], wherein the (II) photocurable monomer and / or oligomer is one or more monomers selected from the group consisting of monofunctional acrylates, difunctional acrylates, polyfunctional acrylates, monofunctional methacrylates, difunctional methacrylates, polyfunctional methacrylates, and urethane acrylates, and / or oligomers of such monomers. [3] The actinic radiation-curable composition according to the above [1] or [2], wherein the content of the vinyl chloride copolymer (I) is 1 to 30 mass% based on the total amount of the vinyl chloride copolymer (I) and the photocurable monomer and / or oligomer (II). [4] The actinic radiation-curable composition according to any one of the above [1] to [3], wherein the vinyl chloride copolymer (I) has a hydroxyl value of 50 to 150 mgKOH / g. [5] The actinic radiation-curable composition according to any one of the above [1] to [4], wherein a coating film formed by curing the actinic radiation-curable composition has a haze value of 2.0% or less. [6] An actinic radiation-curable ink composition comprising the actinic radiation-curable composition according to any one of the above [1] to [5] and a pigment. [7] A coating film obtained by curing the actinic radiation-curable composition according to any one of the above [1] to [5]. [8] The coating film according to [7] above, characterized in that it has a haze value of 2.0% or less. [9] A coating film obtained by curing the actinic radiation-curable ink composition described in [6] above.
[10] An article having a substrate and a coating film formed by curing the actinic radiation-curable composition according to any one of the above [1] to [5].
[11] An article having a substrate and a coating film formed by curing the actinic radiation-curable ink composition described in [6] above.
[12] A method for producing an actinic radiation-curable composition, comprising the step of obtaining an actinic radiation-curable composition by dispersing or dissolving (I) a vinyl chloride-based copolymer in (II) a photocurable monomer and / or oligomer, The vinyl chloride copolymer contains, as a structural unit, (a) 82 to 95 mass% of vinyl chloride-derived units, (b) 0.1 to 5% by mass of units derived from vinyl acetate, and (c) hydroxyl group-containing vinyl-derived unit: 4 to 15% by mass and is free of organic solvents.
[13] The method according to
[12] above, wherein the amount of the (I) vinyl chloride copolymer is 1 to 30 mass% based on the total amount of the (I) vinyl chloride copolymer and the (II) photocurable monomer and / or oligomer. Effect of the Invention
[0013] The actinic radiation curable composition and actinic radiation curable ink composition of the present invention do not contain organic solvents and have excellent flexibility, transparency of the coating film, and adhesion. Therefore, a step of thermally drying the solvent during coating or printing is not required, and there are few environmental concerns. The actinic radiation-curable composition of the present invention provides a coating film having excellent flexibility, transparency, and adhesion, and therefore can be widely used in a variety of applications, including paints for plastics, paper, glass, woodworking, inorganic materials, and the like, coating agents, curable adhesives for packaging materials, display materials, electronic materials, and optical materials, screen printing, offset printing, roll coater printing, and printing inks such as inkjet inks and primer inks. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The actinic radiation-curable composition of the present invention is an actinic radiation-curable composition containing (I) a vinyl chloride copolymer and (II) a photocurable monomer and / or oligomer. The vinyl chloride copolymer contains the following structural units (a) to (c): Vinyl chloride copolymer mass (a) 82 to 95 mass% of vinyl chloride-derived units, (b) 0.1 to 5% by mass of units derived from vinyl acetate, and (c) 4 to 15 mass % of hydroxyl group-containing vinyl-derived units. A copolymer consisting of the above structural units (a) to (c) is preferred.
[0015] Here, (a) vinyl chloride-derived units, (b) vinyl acetate-derived units, and (c) hydroxyl-containing vinyl-derived units are units constituting (I) vinyl chloride copolymers, and are obtained from (a') vinyl chloride monomer, (b') fatty acid vinyl monomer, and (c') hydroxyl-containing vinyl monomer, respectively. (c) Hydroxyl-containing vinyl-derived units may be obtained by saponifying (b) vinyl acetate-derived units.
[0016] The (a) vinyl chloride-derived units impart toughness and high surface hardness to the coating film of the actinic radiation curable composition. The proportion of the (a) vinyl chloride-derived units in the (I) vinyl chloride-based copolymer is preferably 82 to 95 mass% and more preferably 83 to 93 mass% based on the total mass of the vinyl chloride-based copolymer. If the proportion of the (a) vinyl chloride-derived units is less than the above lower limit, the glass transition temperature of the (I) vinyl chloride-based copolymer is low, making it difficult to maintain the particle shape. If the proportion of the (a) vinyl chloride-derived units exceeds the above upper limit, the solubility of the (I) vinyl chloride-based copolymer in the (II) photocurable monomer and / or oligomer is reduced, and the transparency of the actinic radiation curable composition is reduced.
[0017] The proportion of the vinyl acetate-derived units (b) in the vinyl chloride copolymer (I) is preferably 0.1 to 5 mass% and more preferably 1 to 4.5 mass% based on the total mass of the vinyl chloride copolymer. If the proportion of the vinyl acetate-derived units (b) is less than the lower limit, the solubility of the vinyl chloride copolymer (I) in the photocurable monomer and / or oligomer (II) decreases, and the transparency of the actinic radiation-curable composition also decreases. If the proportion of the vinyl acetate-derived units (b) exceeds the upper limit, the glass transition temperature of the vinyl chloride copolymer (I) decreases, and the transparency of the resulting coating film decreases.
[0018] The (c) hydroxyl-containing vinyl-derived unit can be obtained from (c') a hydroxyl-containing vinyl monomer. The (c) component may be a vinyl alcohol unit obtained by saponifying (b) a vinyl acetate-derived unit. Examples of (c') hydroxyl-containing vinyl monomers that give (c) units other than the vinyl alcohol units obtained by saponifying (b) a vinyl acetate-derived unit include hydroxyalkyl (meth)acrylates such as hydroxyethyl vinyl ether, hydroxybutyl vinyl ether, hydroxymethyl (meth)acrylate, and hydroxyethyl (meth)acrylate. These units may be of one type or may contain two or more types.
[0019] The proportion of the (c) hydroxyl-containing vinyl-derived unit in the (I) vinyl chloride copolymer is preferably 4 to 15 mass % and more preferably 5 to 14 mass % based on the total mass of the vinyl chloride copolymer. If the proportion of the (c) hydroxyl-containing vinyl-derived unit is less than the lower limit, the adhesion of the coating film decreases. If it exceeds the upper limit, the transparency of the actinic radiation-curable composition decreases.
[0020] The vinyl chloride copolymer of the present invention may contain vinyl-derived units other than the above components (a), (b) and (c). The vinyl-derived units other than the above components (a), (b) and (c) may be contained in the vinyl chloride copolymer in an amount of 0 to 15% by mass, preferably less than 2.5% by mass. The vinyl chloride copolymer of the present invention preferably contains less than 2.5% by mass, preferably 1% by mass or less, of epoxy-containing vinyl-derived units such as methyl glycidyl methacrylate, methyl glycidyl acrylate, allyl glycidyl ether, allylphenol glycidyl ether and glycidyl methacrylate, and more preferably does not contain the epoxy-containing vinyl-derived units. The vinyl chloride copolymer of the present invention further preferably does not contain vinyl-derived units other than the components (a), (b) and (c).
[0021] The desired vinyl chloride copolymer (I) may be prepared by production or may be a commercially available product. Examples of commercially available products that can be used include the Solvine series manufactured by Nissin Chemical Industry Co., Ltd., the VINNOL series manufactured by Wacker, and the Kanevinyl series manufactured by Kaneka Corporation. Alternatively, the copolymer may be prepared by the method described below.
[0022] The method for producing the vinyl chloride copolymer (I) is not particularly limited. For example, at least (a') vinyl chloride monomer, (b') vinyl acetate monomer, and (c') hydroxyl group-containing vinyl monomer are copolymerized, and (a') vinyl chloride monomer is further added during the copolymerization reaction to produce a vinyl chloride copolymer having a vinyl chloride content of 100% by weight as a structural unit relative to the mass of the vinyl chloride copolymer. (a) 82 to 95 mass% of vinyl chloride-derived units, (b) 0.1 to 5% by mass of units derived from vinyl acetate, and (c) hydroxyl group-containing vinyl-derived unit: 4 to 15% by mass The vinyl chloride copolymer containing the above compound can be obtained.
[0023] In addition, in the case of producing a vinyl chloride copolymer containing a vinyl alcohol unit as a hydroxyl group-containing vinyl-derived unit (c), At least (a') vinyl chloride monomer and (b') vinyl acetate monomer are copolymerized, and (a') vinyl chloride monomer is further added during the copolymerization reaction, followed by a saponification reaction, to obtain, as a structural unit, a vinyl chloride copolymer having a mass of (a') vinyl acetate monomer and (b') vinyl chloride monomer. (a) 82 to 95 mass% of vinyl chloride-derived units, (b) 0.1 to 5% by mass of units derived from vinyl acetate, and (c) A vinyl chloride copolymer containing 4 to 15 mass % of units derived from vinyl alcohol can be obtained. The vinyl chloride copolymer of the present invention may have both vinyl alcohol derived units and other hydroxyl group-containing vinyl derived units, in which case the total amount of the vinyl alcohol derived units and other hydroxyl group-containing vinyl derived units may be 4 to 15% by mass relative to the mass of the vinyl chloride copolymer.
[0024] In addition, each monomer as a raw material may be charged at once before the start of the copolymerization reaction, but some monomers may be added during the copolymerization reaction. The vinyl chloride monomer (a') as a raw material is preferably added during the copolymerization reaction separately from the amount charged before the start of the copolymerization reaction, and the vinyl chloride monomer (a') is preferably added after the temperature is raised. It is preferable that 40 to 80 mass % of the vinyl chloride monomer (a') used as a raw material is added. In this way, a vinyl chloride copolymer (I) having excellent thermal stability and solubility in photocurable monomers and / or oligomers (II) can be obtained.
[0025] The copolymerization reaction is preferably carried out by suspension polymerization. In detail, after the inside of the polymerization vessel is replaced with nitrogen, a polymerization medium, a suspending agent, a polymerization initiator, (a') vinyl chloride monomer, (b') fatty acid vinyl monomer, (c') epoxy group-containing vinyl monomer, and (d') vinyl monomer other than the above components (a'), (b') and (c') are pressurized. Thereafter, the temperature is raised to an appropriate polymerization temperature, and the copolymerization reaction is started under a nitrogen atmosphere. During this copolymerization reaction, each monomer serving as a raw material may be additionally added.
[0026] Examples of the suspending agent include polyvinyl alcohol, partially saponified polyvinyl acetate, cellulose derivatives such as methyl cellulose, ethyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, and hydroxyethyl cellulose, synthetic polymers such as polyvinylpyrrolidone, polyacrylamide, maleic acid-styrene copolymer, and maleic acid-methyl vinyl ether copolymer, natural polymers such as starch and gelatin, polyalkylene oxides such as polyethylene oxide and polypropylene oxide, and oxyethylene-oxypropylene block copolymers. These may be used in combination of two or more kinds.
[0027] The weight average molecular weight of the suspending agent is preferably 50,000 to 5,000,000. For example, polyalkylene oxides such as polyethylene oxide and polypropylene oxide can be suitably used as the suspending agent. The amount of the suspending agent used is preferably 0.05 to 0.3% by mass based on the total amount of the raw material monomers.
[0028] Examples of the polymerization initiator include organic peroxides such as benzoyl peroxide, lauroyl peroxide, 3,3,5-trimethylhexanol peroxide, diisopropyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, diethoxyethyl peroxydicarbonate, di-3-methoxybutyl peroxydicarbonate, butyl peroxyneodecanate, and di-3,5,5-trimethylhexanol peroxide, and azo compounds such as azobisisobutyronitrile and 2,2-azobis(2,4-dimethyl)valeronitrile. Two or more of these may be used in combination. The amount of the polymerization initiator used is preferably 0.1 to 0.3% by mass based on the total amount of the raw material monomers.
[0029] Ion-exchanged water can be used as the polymerization medium. Alternatively, a polymerization medium containing water-soluble alcohol such as methanol or isopropyl alcohol at a ratio of 50% by mass or less may be used. The amount of the polymerization medium used is preferably 50 to 200% by mass based on the total amount of the raw material monomers.
[0030] A chain transfer agent may be used in the copolymerization reaction during the production of the vinyl chloride copolymer (I). As the chain transfer agent, a dihydrooxaphosphaphenanthrene phosphorus compound having a cyclic organic phosphorus compound is preferred. The amount of the chain transfer agent used is preferably 0.3 to 0.6 mass% based on the total amount of the raw material monomers, and more preferably 0.4 to 0.5 mass%. If the amount of the chain transfer agent used is less than 0.3 mass%, the viscosity of the actinic radiation curable composition tends to increase, which may make handling difficult and reduce workability. If the amount of the chain transfer agent used exceeds 0.6 mass%, the physical strength and durability of the coating film of the actinic radiation curable composition may decrease.
[0031] (I) In the copolymerization reaction for producing the vinyl chloride copolymer, the suspending agent, polymerization initiator, chain transfer agent, etc. may be charged all at once before the start of the copolymerization reaction, or may be added during the copolymerization reaction. The polymerization temperature is preferably 50 to 80°C, more preferably 55 to 75°C.
[0032] The vinyl chloride copolymer (I) obtained by the above copolymerization reaction is preferably separated from the polymerization medium, dried, and powdered. The average particle size of this vinyl chloride copolymer powder is preferably 50 to 500 μm. The average particle size is a value measured using a laser diffraction / scattering type particle size distribution measuring device, for example, LA-950V2 (manufactured by HORIBA).
[0033] The average degree of polymerization of the vinyl chloride copolymer (I) is preferably 150 to 800, more preferably 200 to 500, and further preferably 200 to 370. This average degree of polymerization is a value calculated from the results of measuring the time required for a sample dissolved in nitrobenzene to fall at 30.0°C using an Ubbelohde viscometer.
[0034] (I) The number average molecular weight of the vinyl chloride copolymer is preferably 13,000 or more, more preferably 20,000 or more, further preferably 25,000 or more, and particularly preferably more than 25,000. The number average molecular weight is a value measured using a molecular weight distribution measuring device, for example, "GPC-900" manufactured by JASCO Corporation.
[0035] (I) The glass transition temperature of the vinyl chloride copolymer is preferably 60 to 80°C. About 20 mg of the powdered vinyl chloride-vinyl acetate copolymer was measured using a Shimadzu DSC (differential scanning calorimeter) at a heating rate of 5 K / min. Looking at the second heating curve, a baseline shift was observed, and this is the value of the inflection point.
[0036] (I) The vinyl chloride copolymer preferably has a hydroxyl value of 50 to 150 mgKOH / g. More preferably, the hydroxyl value is 50 to 100 mgKOH / g. In the present invention, the hydroxyl value is a value measured by the method of JIS K0070-1992. When the vinyl chloride copolymer has a hydroxyl value in the above range, the solubility in the photocurable monomer and / or oligomer is increased, which is preferable in that the transparency of the coating film is increased when the coating film is formed.
[0037] The actinic radiation-curable composition of the present invention contains (I) a vinyl chloride copolymer and (II) a photocurable monomer and / or oligomer.
[0038] The photocurable monomer and / or oligomer, which is the component (II), is a monomer and / or oligomer that can be polymerized and cured by light having a specific wavelength. As the component (II), those that can be polymerized and cured by ultraviolet light are particularly preferred.
[0039] The (II) photocurable monomer and / or oligomer may be radically polymerizable, cationic polymerizable, or anionic polymerizable, but is preferably radically polymerizable. The (II) photocurable monomer and / or oligomer is preferably one or more monomers selected from the group consisting of monofunctional acrylates, bifunctional acrylates, polyfunctional acrylates, monofunctional methacrylates, bifunctional methacrylates, polyfunctional methacrylates, and urethane acrylates. For example, benzyl acrylate, 2-hydroxy-3-acryloyloxypropyl methacrylate, polyethylene glycol diacrylate, propoxylated ethoxylated bisphenol A diacrylate, 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene, tricyclodecane dimethanol diacrylate, 1,10-decane diol diacrylate, 1,6-hexanediol diacrylate (HDDA), 1,9-nonanediol diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate (TPGDA), polytetramethylene glycol diacrylate, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, ethoxylated bisphenol A dimethacrylate ... dimethacrylate, 1,10-decanediol dimethacrylate, 1,6-hexanediol dimethacrylate, 1,9-nonanediol dimethacrylate, neopentyl glycol dimethacrylate, ethoxylated polypropylene glycol dimethacrylate, glycerin dimethacrylate, polypropylene glycol dimethacrylate, ethoxylated isocyanuric acid triacrylate, ε-caprolactone-modified tris-(2-acryloxyethyl)isocyanurate, pentaerythritol triacrylate, trimethylolpropane triacrylate (TMPTA), ditrimethylolpropane tetraacrylate, ethoxylated pentaerythritol tetraacrylate, pentaerythritol tetraacrylate, dipentaerythritol polyacrylate, dipentaerythritol hexaacrylate, trimethylolpropane trimethacrylate, and the like.In addition, oligomers of these monomers may be used. In this case, the oligomer generally has a degree of polymerization of 10 to 100.
[0040] The actinic radiation curable composition of the present invention preferably contains a photopolymerization initiator together with (II) photocurable monomer and / or oligomer. The photopolymerization initiator generates active species by irradiation with light of a characteristic wavelength, and a suitable one can be selected from photoradical polymerization initiators, photocationic polymerization initiators, and photoanionic polymerization initiators depending on the type of (II) photocurable monomer and / or oligomer. In particular, it is preferable to use a photoradical polymerization initiator that generates radicals by ultraviolet light. Examples of such photopolymerization initiators include alkylphenone-based photopolymerization initiators, acylphosphine oxide-based photopolymerization initiators, intramolecular hydrogen abstraction-type photopolymerization initiators, and oxime ester-based photopolymerization initiators. Among them, alkylphenone-based photopolymerization initiators are preferred, and more specifically, 2,2-dimethoxy-1,2-diphenylethan-1-one, 1-hydroxy-cyclohexyl-phenyl-ketone, 2-hydroxy-2-methyl-1-phenyl-propan-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone, etc. More preferably, α-hydroxyalkylphenone-based photopolymerization initiators such as 1-hydroxy-cyclohexyl-phenyl-ketone, 2-hydroxy-2-methyl-1-phenyl-propan-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, and 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one are preferred. Commercially available initiators include IRUGACURE184, 1173, 2959, and 127 manufactured by BASF.
[0041] The photopolymerization initiator is preferably contained in an amount of 1 part by mass or more, more preferably 1 to 10 parts by mass, based on 100 parts by mass of the total amount of (I) the vinyl chloride copolymer and (II) the photocurable monomer and / or oligomer. If the content is less than 1 part by mass, the actinic radiation curable composition may not be cured.
[0042] The actinic radiation curable composition of the present invention can be obtained by dispersing or dissolving (I) vinyl chloride copolymer in (II) photocurable monomer and / or oligomer. (I) vinyl chloride copolymer is preferably contained in an amount of 1 to 30 mass%, more preferably 20 to 30 mass%, based on the total amount of (I) vinyl chloride copolymer and (II) photocurable monomer and / or oligomer. If the content of (I) vinyl chloride copolymer is less than 1 mass%, the desired effects in flexibility, adhesion, thermal stability, etc. may not be sufficiently obtained. If the content exceeds 30 mass%, (I) vinyl chloride copolymer may not dissolve or the viscosity may become too high.
[0043] The temperature at which (I) the vinyl chloride copolymer is dispersed and dissolved in (II) the photocurable monomer and / or oligomer is preferably 30 to 80°C.
[0044] An actinic radiation curable ink composition can be obtained by dispersing and incorporating a pigment in the actinic radiation curable composition of the present invention. The pigments used are, in terms of color index, Pigment White 4, Pigment White 6, Pigment White 21, Pigment Black 7 (carbon black), Pigment Blue 15, 15:1, 15:3, 15:4, 15:6, 60, Pigment Green 7 (chlorinated phthalocyanine green), 36 (brominated phthalocyanine green), Pigment Red 9, 48, 49, 52, 53, 57, 57:1, 97, 122, 149, 168, 177, 178, 179, 206, 207, 209, 242, 254, 255, Pigment Violet 19, 23, 29, 30, 37, 40, 50, Pigment Yellow 12, 13, 14, 17, 20, 24, 74, 83, 86, 93, 94, 95, 109, 110, 117, 120, 125, 128, 137, 138, 139, 147, 148, 150, 151, 154, 155, 166, 168, 180, 185, 213, Pigment Orange 36, 43, 51, 55, 59, 61, 71, 74, and the like.
[0045] The blending amount of the pigment is appropriately selected depending on the type of pigment, but is usually in the range of 10 to 20 parts by mass per 100 parts by mass of the actinic radiation-curable composition.
[0046] For dispersing the pigment, for example, a ball mill, a sand mill, an attritor, a roll mill, an agitator, a Henschel mixer, a colloid mill, an ultrasonic homogenizer, a pearl mill, a wet jet mill, a paint shaker, or the like can be used.
[0047] The actinic radiation curable composition and actinic radiation curable ink composition of the present invention can be applied onto a substrate by a known method such as spin coating, (doctor) knife coating, microgravure coating, direct gravure coating, offset gravure, reverse gravure, reverse roll coating, (Mayer) bar coating, die coating, spray coating, or dip coating.
[0048] Furthermore, the actinic radiation curable composition and actinic radiation curable ink composition of the present invention can be irradiated with light of a specific wavelength to cure the coating. In this case, the light is preferably ultraviolet light, and the irradiation conditions are an irradiation intensity of 150 to 1,000 mJ / cm. 2 The irradiation time is preferably 1 to 1000 seconds.
[0049] The thickness of the coating film may be appropriately set depending on the purpose, but from the viewpoints of cost and performance, it is preferably 0.5 to 200 μm, and more preferably 1.5 to 100 μm.
[0050] The coating film obtained by curing the actinic radiation curable composition of the present invention preferably has a haze value of 2.0% or less, more preferably 1.8% or less, at a film thickness in the range of 12 to 20 μm. The haze value can be measured using a color difference / turbidity meter COH-400 (manufactured by Nippon Denshoku Industries Co., Ltd.) for a coating film obtained by applying the actinic radiation curable composition to a PET film (manufactured by Toray Industries, Inc.) using a bar coater #10 and curing the film by irradiating it with ultraviolet light having a wavelength of 385 nm for 5 minutes. The smaller the haze value, the higher the transparency of the film, which is preferable.
[0051] When the actinic radiation-curable composition of the present invention contains the above-mentioned pigment, it is possible to provide a coating film having excellent color development properties. The color development properties can be evaluated, for example, by the L value measured using a spectrophotometer.
[0052] The actinic radiation curable composition and actinic radiation curable ink composition of the present invention can be applied to substrates such as plastics such as polyethylene terephthalate (PET), oriented polystyrene (OPS), oriented polypropylene (OPP), oriented nylon (ONy), polyvinyl chloride (PVC), polyethylene (PE), triacetyl cellulose (TAC), polycarbonate, acrylic resin, ABS, polyacetal, polyvinyl alcohol (PVA), and rubbers, as well as metals, paper, wood, glass, and the like.
[0053] Members having a coating film of the actinic radiation-curable composition or the actinic radiation-curable ink composition formed on such a substrate are useful, for example, as flooring materials, floor tiles, various plastic products, beverage cans, metal plates, printed paper, paper containers, record jackets, magazines, aluminum-deposited paper, furniture, wall materials, building materials, optical applications, and the like. EXAMPLES
[0054] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. In the following examples, "parts" refers to "parts by mass".
[0055] In the following, the constituent units of the vinyl chloride copolymer were identified using a near-infrared analyzer (NIRFlexN-500: manufactured by Nippon Buchi Co., Ltd.). In the following, the methods for measuring the various physical properties of the vinyl chloride copolymer are as follows. The hydroxyl value was measured by a method in accordance with JIS K0070-1992. The average degree of polymerization was calculated from the results of measuring the time required for a vinyl chloride copolymer dissolved in nitrobenzene to fall at 30.0° C. using an Ubbelohde viscometer. The glass transition temperature (Tg) was measured for about 20 mg of vinyl chloride copolymer using a DSC (differential scanning calorimeter, manufactured by Shimadzu Corporation) at a heating rate of 5 K / min. The number average molecular weight was measured using a molecular weight distribution analyzer GPC-900 (manufactured by JASCO Corporation). The average particle size was measured using a laser diffraction / scattering type particle size distribution measuring device LA-950V2 (manufactured by HORIBA Corporation).
[0056] [Production Example 1] Into an autoclave equipped with a stirrer, 1030 parts of deionized water, 1030 parts of methanol, 1 part of hydroxypropyl methylcellulose, 9 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 5 parts of di(3,5,5-trimerylhexanoyl)peroxide, and 1 part of t-butyl peroxypivalate were charged. After nitrogen replacement, 644 parts of vinyl chloride monomer and 100 parts of vinyl acetate monomer were charged into the autoclave and stirred. Thereafter, the temperature was raised to 63°C while stirring under a nitrogen gas atmosphere, and immediately after reaching 63°C, 970 parts of vinyl chloride monomer and 315 parts of hydroxypropyl acrylate were continuously injected over 7 hours to allow the copolymerization reaction to proceed. When the pressure inside the autoclave reached 0.22 MPa, the polymerization was terminated, and post-treatment (degassing, deliquation, and drying) was performed to obtain a white powder. The obtained product was a vinyl chloride copolymer having 83.0% by mass of vinyl chloride-derived units, 4.0% by mass of vinyl acetate-derived units, and 13.0% by mass of hydroxyl-containing vinyl (hydroxypropyl acrylate)-derived units. The obtained vinyl chloride copolymer was measured for hydroxyl value, average polymerization degree, glass transition temperature (Tg), number average molecular weight, and average particle size by the above-mentioned methods. The results are shown in Table 1.
[0057] [Production Example 2] Into an autoclave equipped with a stirrer, 1200 parts of deionized water, 1200 parts of methanol, 2 parts of hydroxypropyl methylcellulose, 3 parts of dibenzoyl peroxide, 1 part of di(3,5,5-trimerylhexanoyl) peroxide, and 7 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide were charged. After nitrogen replacement, 580 parts of vinyl chloride monomer and 390 parts of vinyl acetate monomer were charged into the autoclave and stirred. Thereafter, the temperature was raised to 74°C while stirring under a nitrogen gas atmosphere, and immediately after reaching 74°C, 1000 parts of vinyl chloride monomer were continuously injected over 7 hours to allow the copolymerization reaction to proceed. When the internal pressure of the autoclave reached 0.22 MPa, the residual pressure was released, and the resin slurry was cooled and taken out. The resin slurry was filtered and dried to obtain a powdered vinyl chloride-vinyl acetate copolymer (white powder). Next, 1365 parts of methanol, 385 parts of acetone, and 20 parts of sodium hydroxide were stirred and dissolved in a reaction vessel equipped with a stirrer, a condenser, and a thermometer, and then 1000 parts of the white powder obtained above were added and stirred. Then, the temperature was raised to 35°C while stirring, and the saponification reaction was started. The reaction was terminated 3 hours after the start of the reaction, and post-treatment (washing, deliquation, and drying) was performed to obtain a vinyl chloride-based copolymer. The obtained product was a vinyl chloride-based copolymer having 92.5% by mass of vinyl chloride-derived units, 2.5% by mass of vinyl acetate-derived units, and 5.0% by mass of hydroxyl-containing vinyl (vinyl alcohol)-derived units. In addition, the hydroxyl value, average polymerization degree, glass transition temperature (Tg), number average molecular weight, and average particle size of the obtained copolymer were measured. The results are shown in Table 1.
[0058] [Production Example 3] Into an autoclave equipped with a stirrer, 1340 parts of deionized water, 1090 parts of methanol, 1 part of polyethylene oxide (molecular weight 250,000 to 400,000), 2 parts of dibenzoyl peroxide, 1 part of di(3,5,5-trimerylhexanoyl) peroxide, and 11 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide were charged. After nitrogen replacement, 470 parts of vinyl chloride monomer and 430 parts of vinyl acetate monomer were charged into the autoclave and stirred. Thereafter, the temperature was raised to 76°C while stirring under a nitrogen gas atmosphere, and immediately after reaching 76°C, 1100 parts of vinyl chloride monomer were continuously injected over 7 hours to allow the copolymerization reaction to proceed. When the internal pressure of the autoclave reached 0.22 MPa, the residual pressure was released, and the resin slurry was cooled and taken out. The resin slurry was filtered and dried to obtain a powdered vinyl chloride-vinyl acetate copolymer (white powder). Next, 1680 parts of methanol, 320 parts of acetone, and 38 parts of sodium hydroxide were stirred and dissolved in a reaction vessel equipped with a stirrer, a condenser, and a thermometer, and then 1000 parts of the white powder obtained above were added and stirred. Then, the temperature was raised to 40° C. while stirring, and the saponification reaction was started. The reaction was terminated 4 hours after the start of the reaction, and post-treatment (washing, deliquation, and drying) was performed to obtain a vinyl chloride-based copolymer. The obtained product was a vinyl chloride-based copolymer having 92.0% by mass of vinyl chloride-derived units, 1.0% by mass of vinyl acetate-derived units, and 7.0% by mass of hydroxyl group-containing vinyl (vinyl alcohol)-derived units. In addition, the hydroxyl value, average polymerization degree, glass transition temperature (Tg), number average molecular weight, and average particle size of the obtained copolymer were measured by the above-mentioned method. The results are shown in Table 1.
[0059] [Comparative Manufacturing Example 1] Into an autoclave equipped with a stirrer, 1200 parts of deionized water, 1200 parts of methanol, 2 parts of hydroxypropyl methylcellulose, 3 parts of dibenzoyl peroxide, 1 part of di(3,5,5-trimerylhexanoyl) peroxide, and 7 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide were charged. After nitrogen replacement, 580 parts of vinyl chloride monomer and 390 parts of vinyl acetate monomer were charged into the autoclave and stirred. Thereafter, the temperature was raised to 74°C while stirring under a nitrogen gas atmosphere, and immediately after reaching 74°C, 1000 parts of vinyl chloride monomer were continuously injected over 7 hours to allow the copolymerization reaction to proceed. When the internal pressure of the autoclave reached 0.22 MPa, the residual pressure was released, and the resin slurry was cooled and taken out. The resin slurry was filtered and dried to obtain a powdered vinyl chloride-vinyl acetate copolymer. The obtained product was a vinyl chloride copolymer having 86.0% by mass of vinyl chloride-derived units and 14.0% by mass of vinyl acetate-derived units. The hydroxyl value, average polymerization degree, glass transition temperature (Tg), number average molecular weight, and average particle size of the obtained copolymer were measured by the above-mentioned methods. The results are shown in Table 1.
[0060] [Comparative Manufacturing Example 2] In an autoclave equipped with a stirrer, 1070 parts of deionized water, 890 parts of methanol, 1 part of polyethylene oxide, 3 parts of dibenzoyl peroxide, and 1 part of di(3,5,5-trimerylhexanoyl) peroxide were charged. After nitrogen replacement, 590 parts of vinyl chloride monomer and 520 parts of vinyl acetate monomer were charged into the autoclave and stirred. Thereafter, the temperature was raised to 75°C while stirring under a nitrogen gas atmosphere, and immediately after reaching 75°C, 880 parts of vinyl chloride monomer were continuously injected over 7 hours to allow the copolymerization reaction to proceed. When the pressure inside the autoclave reached 0.37 MPa, the polymerization was terminated, and post-treatment (degassing, deliquation, and drying) was performed to obtain a white powder. The obtained product was a vinyl chloride-based copolymer having 79.0% by mass of vinyl chloride-derived units and 21.0% by mass of vinyl acetate-derived units. In addition, the hydroxyl value, average degree of polymerization, glass transition temperature (Tg), number average molecular weight, and average particle size of the obtained copolymer were measured by the above-mentioned methods. The results are shown in Table 1.
[0061] [Table 1]
[0062] [Example 1] 20 parts of the vinyl chloride copolymer (I) from Production Example 1 was dissolved in 80 parts of Miramer M1182 (II) (benzyl acrylate, manufactured by MIWON) by stirring for 3 hours at 60° C. Furthermore, 5 parts of 1-hydroxycyclohexyl phenyl ketone (manufactured by Fuji Film Wako Pure Chemical Industries, Ltd.) was added as a photopolymerization initiator, and the mixture was mixed at 60° C. for 1 hour to obtain an actinic radiation curable composition.
[0063] [Examples 2 to 6, Comparative Examples 1 and 2] The method of Example 1 was repeated except that the raw materials shown in Table 2 or 3 were used, to obtain an actinic radiation-curable composition.
[0064] The solution viscosity, solubility, coating transparency, and adhesion of the obtained actinic radiation curable composition were measured by the following methods. The results are shown in Tables 2 and 3.
[0065] ·Solution viscosity The viscosity of the vinyl chloride copolymer is measured by the following method. A rotational viscometer (BLOOKFIELD DV2T) was used to measure the viscosity. The rotation speed was set to 60 rpm. The vinyl chloride copolymers of Production Examples 1 to 3 and Comparative Production Examples 1 and 2 in the above Examples and Comparative Examples were dissolved in Miramer M1182 (benzyl acrylate, manufactured by MIWON) to a solid content of 20 mass %, and the resulting solution was allowed to stand in a thermostatic bath so that the temperature of the solution was 25°C, after which the viscosity of the solution was measured. From the viewpoint of ease of handling, the viscosity is preferably 1000 to 7000 mPa s.
[0066] ·Solubility In order to confirm the solubility of the solutions prepared by dissolving the vinyl chloride copolymers of Production Examples 1 to 3 and Comparative Production Examples 1 and 2 in Miramer M1182 (benzyl acrylate, manufactured by MIWON Co., Ltd.) to a solid content of 20 mass %, a piece of paper with writing on it was placed as a background, and visually confirmed through the solution whether the writing was visible. (Evaluation Criteria) ○ When the solvent is applied, the text on the back is clearly visible. △ When the solvent is applied, the text behind the image becomes blurred. ×: When the solvent is passed through the label, the text on the back is barely visible.
[0067] Haze value The actinic radiation curable composition was applied onto a PET film (manufactured by Toray Industries, Inc.) using a bar coater #10, and the film was irradiated with ultraviolet light having a wavelength of 385 nm for 5 minutes. The haze value of the film on which the coating film was formed was measured using a color difference / turbidity meter COH-400 (manufactured by Nippon Denshoku Industries Co., Ltd.). The smaller the haze value, the higher the transparency of the film. When a coating film (film thickness after curing: 12 to 20 μm) is formed using the bar coater #10, the haze value is preferably 2.0% or less, and more preferably 1.8% or less.
[0068] Adhesion (cross-cut test) The actinic radiation curable composition was applied onto a PET film (manufactured by Toray Industries, Inc.) using a bar coater #5, and irradiated with ultraviolet light at a wavelength of 385 nm for 5 minutes. At this time, the film thickness after curing was 6 to 10 μm. The film on which the coating was formed was cut into 100 pieces of 2 mm square, and tape peeling was performed. The number of peeled pieces out of 100 pieces was taken as the peeling rate %. The fewer the number of peeled pieces, the higher the adhesion. The peeling rate is preferably 10% or less, and more preferably less than 10%.
[0069] [Table 2]
[0070] [Table 3]
[0071] As shown in Table 2, the coating film obtained from the actinic radiation-curable composition of the present invention is excellent in transparency and substrate adhesion. On the other hand, as shown in Table 3, the actinic radiation-curable composition containing a vinyl chloride copolymer having no hydroxyl-containing vinyl-derived units is inferior in transparency and substrate adhesion to the coating film obtained from the actinic radiation-curable composition of the present invention. Furthermore, the coating film obtained from the actinic radiation-curable ink composition in which a pigment is dispersed and contained in the actinic radiation-curable composition of the present invention is excellent in flexibility, transparency, color development and adhesion.
Claims
1. An actinic radiation curable composition comprising (I) a vinyl chloride copolymer and (II) a photocurable monomer and / or oligomer, the vinyl chloride copolymer (I) containing, as a structural unit, the following relative to the mass of the vinyl chloride copolymer: (a) 82 to 95% by mass of units derived from vinyl chloride, (b) 0.1 to 5% by mass of units derived from vinyl acetate, and (c) Hydroxyl-containing vinyl-derived units: 4 to 15% by mass and is free of organic solvent.
2. 2. The actinic radiation-curable composition according to claim 1, wherein the (II) photocurable monomer and / or oligomer is one or more monomers selected from the group consisting of monofunctional acrylates, difunctional acrylates, polyfunctional acrylates, monofunctional methacrylates, difunctional methacrylates, polyfunctional methacrylates, and urethane acrylates, and / or oligomers of such monomers.
3. 2. The actinic radiation curable composition according to claim 1, wherein the content of the vinyl chloride copolymer (I) is 1 to 30 mass% based on the total amount of the vinyl chloride copolymer (I) and the photocurable monomer and / or oligomer (II).
4. 2. The actinic radiation-curable composition according to claim 1, wherein the vinyl chloride copolymer (I) has a hydroxyl value of 50 to 150 mgKOH / g.
5. 2. The actinic radiation-curable composition according to claim 1, wherein a coating film obtained by curing the actinic radiation-curable composition according to claim 1 has a haze value of 2.0% or less.
6. 6. An actinic radiation-curable ink composition comprising the actinic radiation-curable composition according to claim 1 and a pigment.
7. A coating film obtained by curing the actinic radiation-curable composition according to any one of claims 1 to 5.
8. The coating according to claim 7, characterized in that it has a haze value of 2.0% or less.
9. A coating film obtained by curing the actinic radiation-curable ink composition according to claim 6.
10. 6. An article having a substrate and a coating film formed by curing the actinic radiation-curable composition according to any one of claims 1 to 5.
11. An article having a substrate and a coating film formed by curing the actinic radiation-curable ink composition according to claim 6.
12. A method for producing an actinic radiation-curable composition, comprising a step of dispersing or dissolving (I) a vinyl chloride-based copolymer in (II) a photocurable monomer and / or oligomer to obtain an actinic radiation-curable composition, wherein the vinyl chloride-based copolymer contains, as a structural unit, (a) 82 to 95% by mass of units derived from vinyl chloride, (b) 0.1 to 5% by mass of units derived from vinyl acetate, and (c) Hydroxyl-containing vinyl-derived units: 4 to 15% by mass and is free of organic solvents.
13. The method according to claim 12, wherein the amount of the vinyl chloride copolymer (I) is 1 to 30% by mass based on the total amount of the vinyl chloride copolymer (I) and the photocurable monomer and / or oligomer (II).
Citation Information
Patent Citations
Radiationnhardenable dispersion containing substantially nonpolymerizable high molecular vinyl resin
JP1981011905A
Laminating ultraviolet curing printing ink composition
JP1987205174A
Active ray curable composition, active ray-curable ink composition and method for producing them
JP2018135483A
Decorative sheet
JP2023138508A
Electrically conductive ink, electrically conductive circuit, and noncontact-type medium
WO2006095611A1